Re-description of Coeliccia erici Laidlaw, and the description of Coeliccia sameerae sp. nov. from Peninsular Malaysia (Odonata: Zygoptera: Platycnemididae) - Dow, Rory A.; Choong, Chee Yen; Ng, Yong Foo (Zootaxa, 2018)
Coeliccia erici Laidlaw, 1917 is re-described and illustrated for both sexes; its taxonomic history and the confusion surrounding it is discussed. Coeliccia kimurai Asahina, 1990 is shown to be a junior synonym of C. erici. Coelicca sameerae sp. nov. (holotype ♂, small stream near Sungai Lasir, Tasik Kenyir, Terengganu, Malaysia, deposited in the Natural History Museum, London) is described from both sexes from Peninsular Malaysia; this species had been confused with C. erici until now. A remark on the status of Coeliccia simillima Laidlaw, 1917 is made.